The Role of Entrepreneurship in Driving Sustainable Development - Ogy Mahendra (Jurnal EduHealth, 2023)
Sustainable development is the main focus of the global agenda to overcome increasingly complex environmental, social and economic challenges. Entrepreneurship is considered as one of the driving forces in efforts to achieve sustainable development, because it has the potential to create innovation, economic growth and solutions to social and environmental problems. This research aims to examine the role of entrepreneurship in encouraging sustainable development. This research uses a qualitative approach by analyzing related literature as well as case studies of entrepreneurship that contribute to sustainable development. The results of this research confirm that entrepreneurship has a major role in encouraging sustainable development. Entrepreneurs not only create jobs and sustainable economic growth, but also become a source of innovation to address complex environmental and social problems. They integrate sustainable principles in their business, provide concrete solutions to social problems, and are actively involved in their communities. Thus, entrepreneurship is not just about business, but also about being an agent of change that helps achieve broader sustainable development goals.